Spying for dummies. - Oberc, J.
This paper describes how, in their quest to make the world more visible, commercial imaging companies may well be blind to some uncomfortable features of that world, especially people's ability to find harmful uses for any new tool, and the temptation to fight over any new valuable resource. If history is any indication, the flourishing of commercial space imaging systems will bring with them not only the marvelous benefits, but also the threat that someday the so far meaningless term ?first space war? will finally refer to something real
Keywords: Commercial space imaging systems; Defence implications; Military applications; Satellite imaging